Recovery of a Malaysian recombinant Newcastle disease virus strain - Kavitha, Murulitharan; Khatijah, Yusoff; Omar, Abdul Rahman; Molouki, Aidin (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
Newcastle disease virus strain AF2240 is a viscerotropic velogenic strain that is used as a vaccine challenge virus in Malaysia. The identification of the full length genome will be a crucial platform for further studies of this isolate. In this study, we fully sequenced the genome of a derivative of this strain named AF2240-I. The 15,192 nt long genome contains a 55-nt leader sequence at the 3’ whereas the trailer region consists of 114-nt at the 5’. The intergenic sequences between the NP-P, P-M, M-F, F-HN and HN-L genes comprise 1, 1, 1, 31, and 47 nt respectively. The acknowledged cleavage site of fusion protein showed amino acid sequence of 112-R-R-Q-K-R-F-117 which corresponds to those of virulent NDV strains. Phylogenetic analysis of the whole virus genome showed that the strain AF2240-I belongs to genotype VIII and is more closely related to velogenic strains QH1, QH4, Fontana, Largo and Italien than to other strains of NDV. Differences were noticed in the HN and M gene between AF2240 and its derivative AF2240-I. This is the first report of a complete genome sequence of an NDV strain isolated in Malaysia.